2019
DOI: 10.1016/j.bjpt.2018.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Steps, duration and intensity of usual walking practice during subacute rehabilitation after stroke: an observational study

Abstract: ACTRN12613000764730 (https://www.anzctr.org.au/Trial/Registration/TrialReview.aspx?id=364545).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…10 Therefore, interventions aimed at improving walking speed, such as treadmill training, body-weight support training, cueing of cadence, and virtual reality, 32---34 and increasing the intensity of walking practice should be encouraged during rehabilitation, as they may have an impact on locomotion ability. 35 Previous studies have demonstrated that better locomotion ability is associated with improved community ambulation and increased social participation. 5,36 It is important to highlight that the mean time since the onset of the stroke in the present study was six years, and other factors, such as the ability to control the trunk, sitting balance, and functional status might be related to locomotion ability in individuals at the initial post-stroke phases (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…10 Therefore, interventions aimed at improving walking speed, such as treadmill training, body-weight support training, cueing of cadence, and virtual reality, 32---34 and increasing the intensity of walking practice should be encouraged during rehabilitation, as they may have an impact on locomotion ability. 35 Previous studies have demonstrated that better locomotion ability is associated with improved community ambulation and increased social participation. 5,36 It is important to highlight that the mean time since the onset of the stroke in the present study was six years, and other factors, such as the ability to control the trunk, sitting balance, and functional status might be related to locomotion ability in individuals at the initial post-stroke phases (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…These percentages reinforce the need for modified physical therapy in patients with severe stroke-related symptoms 42 ; including early and targeted management, and long-term daily care. 3,11,15,43,44 Individuals with LMI showed appropriate response to standard treatment, but the proportion of patients who received physical therapy could clearly be improved. Their mild severity of the stroke symptoms and delayed onset of PSSP may explain the low number of referrals to physical therapy.…”
Section: Discussionmentioning
confidence: 99%
“…They may not need an urgent rehabilitation approach, but a longer follow-up including detailed shoulder kinematic tests 45,46 and trunk muscle strength assessment. 47 Despite the importance reported by previous studies 43,48 on the intensity of the rehabilitation, physical therapy interventions could not be analyzed because we cannot guarantee that all participants with PSSP received the same approach and the data related to the procedures may be incomplete. Additionally, we focused pain assessment on pain related to glenohumeral movement ---strongly associated with PSSP diagnosis ---and response to treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Parkinson's disease (Mattson, 2012), psychosis (Hallgren et al, 2019), major depressive disorder (Gujral et al, 2019), and stroke (Beez & Steiger, 2019;Kuys, Ada, Paratz, & Brauer, 2019;Steen Krawcyk et al, 2019).…”
Section: The P Otential Of Phys I C Al E Xercis E To Pre Vent and Tmentioning
confidence: 99%
“…Physical exercise has been investigated as adjuvant therapy in the context of several neurological and neurodegenerative diseases, including AD (Okonkwo et al., 2014; Winchester et al., 2013), Parkinson's disease (Mattson, 2012), psychosis (Hallgren et al., 2019), major depressive disorder (Gujral et al., 2019), and stroke (Beez & Steiger, 2019; Kuys, Ada, Paratz, & Brauer, 2019; Steen Krawcyk et al, 2019).…”
Section: The Potential Of Physical Exercise To Prevent and Treat Demementioning
confidence: 99%